Hubungan Antara Konsep Diri Dengan Kepercayaan Diri Remaja Yang Mengunggah Foto Selfie Di Instagram (Ditinjau Dari Jenis Kelamin Dan Usia) - Nurika, Bunga, Setia Asyanti S.Psi, M.Si (2016)
Self confidence is someone's reliance about the ability of themselves, not depended to others, capable of having positive thought so that the individuals can be responsible for what they did and see the reality through of objective way. Self confidence is influenced by several factors, including self concept. The purpose of this research is to get to know the relationship between self concept with self confidence in adolescents whom uploaded their photo selfie in instagram and to get to know the differences of self confidence reviewed from gender and age. Hypothesis on this research is that (a) there is a positive relationship between selfconcept with self confidence; (b) there is a differences of self confidences reviewed by gender; (c) there is a differences of self confidences reviewed by age. This research was conducted at SMPN 04 Tambun Selatan and SMAN 3 Bekasi. The subject of this research is the student of SMPN 04 Tambun Selatan with 70 students in age of 14-15 years old and students of SMAN 3 Bekasi with 72 students in age of 16-18 years old. Total subject in this study were 142 students and taken using cluster random sampling technique. Measuring instrument that was used is a scale self confidence and self concept. Data analysis techniques using correlation analysis product moment and independent sample T-test. The results of this research obtained (a) there is a very significant positive relationship between self concept with self confidence, it means more positive self concept which is have the higher in self confidence; (b) there is a differences of self confidences reviewed by gender, it means a man has a higher self confidences than female; (c) there is a differences of self confidences reviewed by age, it means 16-18 years old has a higher self confidences than 14-15 years old; (d) self concept contributed to self confidence of r2 = (0,480)2 = 0,230, SE = 23%. Both variables namely, self concept and self confidence are being classified by average. The result of this research implies the importance of self concept of themselves against self confidence in adolescents whom uploaded their photo selfie in instagram. The results will be discussed in the text of this publication. Keywords : Self Concept, Self Confidence, Adolescent